2014
DOI: 10.1590/0103-8478cr20131670
|View full text |Cite
|
Sign up to set email alerts
|

Escarificação e adubação orgânica: efeito na recuperação estrutural de solo produzindo Tifton 85

Abstract: RESUMO A produção intensiva de forrageiras para fenação aumenta os riscos de degradação física do solo e a escarifi cação, INTRODUÇÃOO incentivo de órgãos governamentais e não governamentais à produção de leite no sudoeste do Paraná acarretou em aumento de áreas com cultivo de forrageiras para fenação, principalmente a Tifton 85 (Cynodon dactylon). Na região, o cultivo da Tifton 85 é realizado, geralmente, em solos de textura muito argilosa e, devido ao intenso tráfego de máquinas, muitas vezes sem controle da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
1
10
0
4
Order By: Relevance
“…Furthermore, there was a probable influence of the soil compaction, which can be induced the fragmentation of macropores into micropores. The values were similar to those observed by Magalhães et al (2009) in an Ultisol, but distinct to the results obteined by Colussi, Silva and Minato (2014), in a Alfisol cultivated with Tifton 85 and located in the Southwest region of the state of Paraná, Brazil. These authors found values for Micro above 0.46 m 3 m -3 , which can be associated to the distinct soil class and the scarifier use, which implies soil structural changes.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, there was a probable influence of the soil compaction, which can be induced the fragmentation of macropores into micropores. The values were similar to those observed by Magalhães et al (2009) in an Ultisol, but distinct to the results obteined by Colussi, Silva and Minato (2014), in a Alfisol cultivated with Tifton 85 and located in the Southwest region of the state of Paraná, Brazil. These authors found values for Micro above 0.46 m 3 m -3 , which can be associated to the distinct soil class and the scarifier use, which implies soil structural changes.…”
Section: Resultssupporting
confidence: 87%
“…has been prominent among other forage grasses. This specie is characterized by a dense root system with fast renewal, which confers the capacity of the biological soil decompression and the structure recovery of physically degraded soils (MAGALHÃES et al, 2009;COLUSSI;MINATO, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essa gramínea é caracterizada por um sistema radicular robusto e com rápida renovação, atuando na descompactação biológica do solo. Esses fatores permitem, ainda, o emprego da espécie como um instrumento para recuperação de solos fisicamente degradados (COLUSSI et al, 2014).…”
Section: Introductionunclassified